60Co γ-rays irradiation modified p-diethynylbenzene as prepolymers to prepare polyarylacetylene with excellent heat resistance. (April 2015) - Li, Qianqian; Yu, Ruobing; Zhu, Changjin; Jiao, Zheng
Abstract: Modified p-diethynylbenzene (p-DEB) by 60 Co γ-rays irradiation (γ-p-DEB) was utilized as prepolymer of polyarylacetylene (PAA) for the first time. The composition, structures and properties of prepolymers (γ-p-DEB) and the corresponding cured PAA resins (γ-PAA) have been investigated by mass spectrometry (MS), ultraviolet and visible spectrophotometry (UV), Fourier transform infrared (FT-IR) spectra, differential scanning calorimetry (DSC) and solid-state 13 C MAS NMR. The thermal properties have been studied by thermogravimetry (TGA). Compared with unmodified p-DEB, dimers and trimers appear in γ-p-DEB samples and with the irradiation dose increasing, the content of conjugated structures is on the increase. γ-p-DEB samples possess lower reaction heat and apparent activation energy of thermal polymerization，achieving the goal of avoiding explosion. γ-PAA samples show better heat resistance than PAA prepared from unmodified p-DEB, corresponding to lower sp content than PAA. Moreover, post-radiated PAA and γ-PAA have better heat resistance than PAA and γ-PAA, due to higher cross-linking density and lower residual triples. γ-rays irradiation is an effective way for improving the comprehensive properties of PAA.